Pharmaceutical Care Increases Time in Therapeutic Range of Patients With Poor Quality of Anticoagulation With Warfarin - Marcatto, Leiliane Rodrigues; Sacilotto, Luciana; Tavares, Letícia Camargo; Facin, Mirella; Olivetti, Natália; Strunz, Celia Maria Cassaro; Darrieux, Francisco Carlos Costa; Scanavacca, Maurício Ibrahim; Krieger, Jose Eduardo; Pereira, Alexandre Costa; Santos, Paulo Caleb Junior Lima (Frontiers in Pharmacology, 2018)
Thromboembolic events are associated with high mortality and morbidity indexes. In this context, warfarin is the most widely prescribed oral anticoagulant agent for preventing and treating these events. This medication has a narrow therapeutic range and, consequently, patients usually have difficulty in achieving and maintaining stable target therapeutics. Some studies on the literature about oral anticoagulant management showed that pharmacists could improve the efficiency of anticoagulant therapy. However, the majority of these studies included general patients retrospectively. The aim of this study was to prospectively evaluate a pharmacist’s warfarin management in patients with poor quality of anticoagulation therapy (Time in the Therapeutic Range- TTR<50%). We included 268 patients with atrial fibrillation and without stable dose of warfarin (TTR <50%, based on the last three values of International Normalized Ratio-INR). We followed them up for 12 weeks, INR values were evaluated and, when necessary, the dose adjustments were performed. During the first four visits, patient’s INR was measured every 7 days. Then, if INR was within the target therapeutic range (INR: 2-3), the patient was asked to return in 30 days. However, if INR was out the therapeutic target, the patient was asked to return in 7 days. Adherence evaluation was measured through questionnaires and by counting the pills taken. Comparison between basal TTR (which was calculated based on the three last INR values before prospective phase) and TTR of 4 weeks (calculated by considering the INR tests from visit 0 to visit 4, in the prospective phase of the study) and basal TTR and TTR of 12 weeks (calculated based on the INR tests from visit 0 to visit 12, in the prospective phase of the study) revealed significant statistical differences (0.144±0.010 vs 0.382±0.016; and 0.144±0.010 vs 0.543±0.014, p<0.001; respectively). We also observed that the mean TTR of 1 year before (retrospective phase) was lower than TTR value after 12 weeks of pharmacist-driven treatment (prospective phase) (0.320±0.015; 0.540±0.015, p<0.001). In conclusion, pharmaceutical care was able to improve TTR values in patients with atrial fibrillation and poor quality of anticoagulation with warfarin.